ANALISIS PENGARUH KUALITAS PELAYANAN, PERSEPSI HARGA DAN KEPERCAYAAN TERHADAP MINAT BELI ULANG (Studi Pada Pengguna XL Semarang) - Primandesera, Andika; Sukresna, I Made (Diponegoro Journal of Management, 2018)
Technology has been growing fast over the years, especially on communication, such as mobile phone. The number of mobile phone users in Indonesia increased more than the number of its population. This indicates, people are using more than one mobile phone. However, XL as one of the oldest phone services operator has a decreased on their users based on their annual report. Also, there are some complaints from their users. Therefore, XL needs to increase repurchase intention of their users. This study aims to analyze repurchase intention level of XL through service quality, perceived price and trust with perceived value as an intervening variable.Population of this study is all of XLâ€™s users at Semarang. The sample used for this research must be at least 17 years of age. This study conducted on 140 respondents by using non-probability purposive sampling technique. Â This study conducted 5 variables, 16 indicators and 4 hypotheses.The analysis technique used for this research are factor analysis with SPSS and structural equation models with AMOS program. The results of this study show that service quality has positive and significant correlation on perceived value. Perceived price has positive and significant correlation on perceived value. Trust has positive influence and significant correlation on perceived value and perceived value has positive and significant correlation on purchase intention. Also, this study shows that service quality is the most influential variable on repurchase intention through perceived value.